Recent Publications (Quarterly Journal of Economics, 1955)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 69, Issue 1, February 1955, Pages 157–159, https://doi.org/10.1093/qje/69.1.157 Published: 01 February 1955